PENGAMBILAN KEPUTUSAN DAN SIKAP KONSUMEN RUMAH TANGGA DALAM MEMBELI BERAS SIGER TOGA SARI DAN MEKAR SARI - Annisa Parastry; Dyah Aring Hepiana Lestari; Fembriarty Erry Prasmatiwi (Lampung University, 2017)
This research aims to analyze the stages of decision-making and consumer’s attitude on buying siger rice Toga Sari and Mekar Sari. This research was conducted by a survey at Villages of Wira Agung Sari, Subdistrict of Penawartama of Tulang Bawang Regency, and at Villages of Margorejo, Subdistrict of South Metro of Metro City. These villages were selected on purpose. Research data was collected in August until November 2015. The number of respondents in this research as many as 89 were chosen by accidental sampling method. The data was analyzed by descriptive qualitative and multiatribute Fishbein. The results showed that the decision-making on buying siger rice by the household consumers was began by the state of introduction in which consumer needs of siger motivated to consume rice for some reasons, i.e benefits achieved. Most consumers know rice siger information through the family and evaluate the benefits of the product to be an attribute that the primary consideration in buying. The majority of consumers buy siger yellow rice with the distance to the place of purchase one to five kilometers , and evaluate post-purchase consumers were satisfied in buying rice siger and still buy rice siger despite the price increase on the grounds provide health benefits. The results of the multiatribute Fishbein analysis, household consumer’s attitude in buying siger rice Toga Sari really like, while the siger rice Mekar Sari shows the attitude is like. Key words: consumer attitudes, decision making, siger rice